The antecedents and consequences of divorce cases among employees during covid-19 in Malaysia - Parrimala, Moorty (2023)
The antecedents and consequences of divorce cases among employees in Malaysia during COVID- 19 have been reviewed, along with some plausible study aims and conclusions. The aims of the study are in line with its goal, which strengthens the justification for this research. The research studies indicate who was impacted during the Covid-19 pandemic. The research objective has focused on analyzing the high number of divorce cases among employees during the pandemic situation. In this regard, the relevant causes of filling many divorce cases in Malaysia have been elaborated. To decrease the number of divorces, government programs, self-care, and efficient communication to strengthen social worries have been advocated. The proposed research framework, the research philosophy and research approach were discussed. In addition, the research's design, sample, and population are also brought up in this research. The study explains the facts and potential issues of a stressed-out family from the perspective of divorce proceedings. The study explains the facts and the possible challenges of a family going through stress from the point of view of divorce cases. The findings have identical research objectives and analysis, and it also evaluates multiple factors that are helpful while conducting the research. Furthermore, the findings share the same study aims and analysis, and it examines a variety of criteria that are useful when performing the research. In this study, five research findings were chosen and addressed using different diagrams and the experiences and concerns of different informants. Finally, the study provided a qualitative and detailed analysis so that productive employees can be helpful and overcome their condition.